5G Coverage Planning for Urban Area at Kathmandu City, Nepal - Sharma, Nirmala; Shakya, Subarna (Journal of Electronics and Informatics, 2022)
The excitement about the 5G wireless network has passed. Mobile network operators (MNO) have begun rolling out 5G networks alongside 4G cellular networks in lower frequency and mid-frequency bands (i.e., 3-6 GHz) all over the world. The mid-frequency band can greatly improve the performance of the current network (i.e., 50 MHz–100 MHz). All we know that the wider spectrum can be provided by the high frequency bands which is required to fulfill the greatest bitrates (20 Gb/s), lowest latencies, and constantly increasing capacity demands. The free space propagation loss rapidly increases as we move to higher frequency bands, that will reduce the individual cell site radius to 100 m for the high frequency band from various distances in 4G. To offer consistent 5G coverage, the MNOs will have significant challenges in precisely planning and acquiring these enormous numbers of new cell site locations. This paper describes about the signal characteristics at 800MHz, 1800MHz for 4G and at 700MHz, 2300MHz, 2600MHz, 3500MHz for 5G and the upgradation of 4G towards 5G in the test environment. The 5G Coverage Planning with three sector cells and its SINR Mapping in advance antenna array will be performed to provide better coverage in 5G environments.
Keywords: 4G; 5G; massive MIMO; 5G Coverage Planning; antenna array; SINR Mapping; millimeter-wave